Linguistodicatic basis of training specialist translators based on information resources - Bakirova Khilolakhon Botirlaiyevna (Goodwood Publishing, 2025)
Purpose: This study aims to examine the linguodidactic foundations for training professional translators in the digital era, with a focus on the integration of information resources to enhance the effectiveness of specialized translation education. Methodology/approach: The research employs a qualitative descriptive approach through a review of existing theories, case studies, and pedagogical practices in translator education. It analyzes the use of information and communication technologies (ICT), including electronic corpora, terminology databases, and machine translation tools, in various domains such as legal, medical, and technical translation. Results/findings: Findings indicate that the incorporation of ICT and digital resources significantly improves translator training outcomes. Students develop stronger terminological precision, higher efficiency in handling specialized texts, and greater adaptability to technological innovations. Furthermore, the integration of electronic resources supports collaborative learning and problem-solving strategies in professional contexts. Conclusion: The use of ICT-based information resources provides a solid theoretical and practical framework for enhancing translator education. However, successful implementation requires balanced integration with traditional pedagogical methods to avoid overdependence on automated tools. Limitations: The study is limited by its reliance on secondary literature and lacks empirical testing through experimental or longitudinal research in classroom settings. Contribution: This paper contributes to the field of translation studies by providing a comprehensive model of how digital resources can be effectively integrated into linguodidactic approaches for specialized translator training, offering valuable insights for curriculum developers and educators.